Gregory of Nyssa: ancient and (post)modern - Ludlow, Morwenna (Oxford University Press, 2007)
The fourth-century Christian thinker Gregory of Nyssa has been the subject of a huge variety of interpretations over the past 50 years. Morwenna Ludlow analyses these readings, questioning what they reveal about modern and postmodern interpretations of the Christian past, and what they say about the nature of Gregory's writing